El nacimiento de una Nación como crisis cultural: Estados Unidos, 1919-1941 - Francisco Javier Caspistegui (Memoria y Civilización, 2007)
This article will examine the way in which a set of cultural characteristics put down their roots and finally defined the US as a nation during the interwar period. The wish to be different from the European cultural models was seen in the explicit differences and in the construction of their own distinct culture, with clear effects in all areas: political, social and intellectual.